Prevalence of Breast Cancer in Female Physicians Performing Procedures With Significant Fluoroscopy Exposure: Survey. Issue 5 (1st September 2021) - Biglione, Bianca; Nakhaei, Masoud; Hamilton, Barbara; Englander, Meridith J.; Dua, Anahita; Brook, Olga R.
Abstract : Objective: The aim of this study was to assess self-reported breast cancer prevalence potentially associated with occupational radiation exposure from fluoroscopy-guided procedures in female physicians using current standard protection measures. Methods: An institutional review board–approved survey was shared as a link to self-identified female physicians. We compared self-reported prevalence of breast cancer among women physicians with longer than 10 years of postfellowship practice in specialties with heavy fluoroscopy exposure versus specialties with low fluoroscopy exposure. We compared the distribution of breast cancer risk factors and personal radiation safety measures. Results: A total of 303 women physicians participated in the survey. There were 8 (16%) of 49 from the first study group and 8 (18%) of 44 from the second study group who self-reported a diagnosis of breast cancer. There were no differences in the distribution of breast cancer risk factors between the 2 groups or prevalence of breast cancer ( P = 0.81). Conclusions: Self-reported breast cancer prevalence is similar between women physicians who are practicing fluoroscopically heavy and light medical specialties.